SMALL AND MEDIUM ENTERPRISES (SMES) – DETERMINANTS FOR INTELLIGENT GROWTH AND SUSTAINABLE DEVELOPMENT OF LOCAL COMUNITIES - Constantin BRAGARU (Challenges of the Knowledge Society)
The EU Cohesion Policy faced many challenges over the last five years, especially because of the long-term consequences of economic crisis. The recession generated regional and intra-regional disparities within European Union and undoubtedly created economic and social contrasts between member states. In order to remedy this situation, European Union reformed its Cohesion Policy for the next period of time, 2014-2020, focusing on fewer key priorities mainly on investments in local growth, capabilities, local economic potential and support for small and medium-sized enterprises. The present paper presents the impact of economic crisis on European SMEs and, in particular, on the Romanian SMEs decline. The article also highlights the Romanian SMEs perspectives in terms of financial support that will be provided by the European Reformed Cohesion Policy for the next six years to come in order to build sustainable local communities.